Emotional Regulation Play Therapy for Maltreated Children: A Single Case Study - Juliana Marlin Y Benu (Journal of Health and Behavioral Science, 2023)
Aggressive children's behavior can arise from the child's inability to regulate the emotions that are felt as a result of the violence they have experienced as one form of maltreatment. This study aims to see how Emotional Regulation Play Therapy affects the behavior of maltreated children. This study was a quasi-experiment with a single case pre-test and post-test design. The participant of this study was a 10 years old boy with physical abuse and neglect history. Emotional Regulation Play Therapy consists of 5 therapy sessions based on emotional regulation development steps by Knell (2009). Measurement of emotional regulation ability was carried out using the Emotional Regulation Questionnaire for Child and Adolescence (ERQ-CA) developed by Gullone and Taffe (2011). The measurement results show an increase in the ERQ-CA score by 19 points accompanied by an increase in the ability to regulate emotion which is described qualitatively.